Talent Development Programs for Secondary Schools: Implementation and Evaluation of a Model School - Gregor Jöstl; Sara Hinterplattner; Silke Rogl (MDPI AG, 2023)
A school profile of talent development including model classes has been implemented at BG/BRG Keimgasse. This paper evaluates the impact of the actions taken by the school and compares the effects of both the model classes and the regular classes, with a school without a special focus on talent development. The aim of this study was to investigate the influence that the change in profile and teaching strategies had on both types of classes. This was conducted through initial qualitative interviews, followed up by quantitative questionnaires. It was found that the model classes had significantly higher scores in terms of school satisfaction, class climate, self-efficacy, mastery goal orientation, and in hope of successes, as well as scoring significantly lower on classroom pressure. This was achieved while shortening the education for the model-class students by one year and adding extracurricular activities. When comparing the regular classes at BG/BRG Keimgasse with classes from a regular school, the scores differed only slightly. This suggested that the concepts integrated at BG/BRG Keimgasse were successful in catering to the gifted students, without compromising the quality of the regular education.